Pengaruh Pelatihan Imagery dan Konsentrasi Terhadap Percaya Diri dan Motivasi Berprestasi Atlet Taekwondo - Okik Hadi Saputro; I Wayan Artanayasa; Suratmin Suratmin; I Ketut Sudiana; Kadek Yogi Parta Lesmana (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to: (a) To determine the difference in the effect of imagery training on self-confidence and achievement motivation of Dojang Udayana taekwondo athletes. (b) To determine the difference in the effect of concentration training on self-confidence and achievement motivation of Dojang Udayana taekwondo athletes. (c) To determine the difference in the effect of imagery training and concentration training on self-confidence and achievement motivation of Udayana Dojang taekwondo athletes. This research is pure experimental research. The subjects in this study were athletes at Dojang Udayana Badung Regency totaling 30 people. The instrument used in this research is a questionnaire. While the data analysis technique used in this research is paired sample t test analysis.